HISTORY OF DEVELOPMENT AND CURRENT TRENDS INDIVIDUALIZATION OF TEACHING IN PEDAGOGICAL THOUGHTS OF THE PAST AND THE PRESENT (Pedagogy of Higher and Secondary Education, 2002)
The article deals with the history of individual approach in training and present-day state of given problem.